‘Watch the Flu’: A Tweet Monitoring Tool for Epidemic Intelligence of Influenza in Australia - Jin, Brian; Joshi, Aditya; Sparks, Ross; Wan, Stephen; Paris, Cécile; MacIntyre, C Raina (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
‘Watch The Flu’ is a tool that monitors tweets posted in Australia for symptoms of influenza. The tool is a unique combination of two areas of artificial intelligence: natural language processing and time series monitoring, in order to assist public health surveillance. Using a real-time data pipeline, it deploys a web-based dashboard for visual analysis, and sends out emails to a set of users when an outbreak is detected. We expect that the tool will assist public health experts with their decision-making for disease outbreaks, by providing them insights from social media.